Physical performance tests in the prognosis of adverse outcomes in the elderly - Daysi García Agustín; Caridad de Dios Soler Morejón; Zenén Rodríguez Pérez (Centro Provincial de Información de Ciencias Médicas, 2018)
Physical performance tests are objective measurements of the functional state of the elderly, and their effectiveness has been demonstrated to identify who of them are more susceptible to disability. The advantages of implementing these tests in the geriatric clinical practice are exposed in this work, which are feasible in any scenario, even with few resources conditions, due to their simplicity, reproducibility and low cost; so that they can be more used to stratify the disability risk in aged patients of any community.